Promoting Goodwill and Universal Humanism through Storytelling; the Ibuanyidanda Philosophical Initiative - OKORO, Lilian (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2024)
In recent years, the tradition of storytelling has experienced a significant decline, raising concerns due to its historical role as a primary vehicle for enlightenment. The aftermath of the COVID-19 pandemic has exacerbated this decline, characterized by increased social isolation and diminished communal relationships. Economic challenges and urban lifestyles have further eroded opportunities for family storytelling sessions. The adage “if you are not informed, you will be deformed” underscores the urgency of revitalizing storytelling, particularly for children and youth. This paper advocates for the collection and documentation of stories aimed at young audiences, emphasizing the incorporation of the Ibuanyidanda concept. This concept promotes unity and understanding, aligning with the principle of 'Igwebuike' (unity is strength) among youths. Methodologically, the paper reviews stories with themes relevant to Ibuanyidandaism, highlighting their potential to instill courage for teamwork and peaceful coexistence in the post-pandemic era. Findings suggest that families engaged in storytelling develop deeper mutual understanding, especially regarding sensitive topics, and find solace in narratives with positive outcomes. Asouzu Ibuanyidanda's theory provides theoretical grounding for this paper. In conclusion, fostering storytelling across various platforms in the digital age offers a promising avenue for promoting universal humanism, goodwill, and understanding among young people.